ANALISIS KEMAMPUAN TANAH DI DAERAH PEMUKIMAN KOTA BENGKULU DALAM MENJERAP ALKYL BENZENE SULPHONATE (ABS) DAN LINEAR ALKYLBENZENE SULPHONATE (LAS) - Fikri Ananda; I Nyoman Candra; Elvinawati Elvinawati (University of Bengkulu, 2019)
This research aims to know the ability of land in a residential area of the city of Bengkulu in adsorbed Alkyl Benzene Sulphonate (ABS) and Linear Alkyl Benzene Sulphonate (LAS). Soil samples were taken at five-point i.e. the backyard of Balai Buntar, Fatmawati Airport, Beringin Raya , Pematang Gubernur and Simpang Nakau with a drill ground at a depth of 20 cm and cleaned from garbage impurity. Then the soil characterized include moisture content, pH, texture and the organic content and ABS and ALS adsorbsition measured using UV-vis spectrophotometers att 222-223 nm wavelengths. In this research tested the influence of pH, pulp and optimum contact time contacts from soil sample at in ABS and ALS adsorbsition The adsorbtion pattern is known as the Freundlich and Langmuir parameters. Based on research, generally, it can be concluded that the land in the residential area of Bengkulu city has characteristic average water content – average 23%, pH average – average 5.35 and it's Turn dusty clay. The optimum condition from soil in adsorbs from Alkyl Benzene Sulphonate (ABS) occurs at pH 3, a mass of 1 g and 2 hours of contact time with the adsorption capacity of 0.874 mg/g, while for Linear Alkyl Benzene Sulphonate (LAS) adsorption the optimum soil conditions occur at pH 2, mass 0.5 g and 1-hour contact time with the adsorption capacity of 1.607 mg/g. The pattern of soil adsorption against ABS tends to follow the Langmuir equation whereas against LAS tend to follow the Freundlich equation. Adsorpstion of soil samples in Bengkulu City against ABS belongs to low and adsorpstion against LAS belongs to very low